Comparison of Advanced Threshold and SITA Fast Perimetric Strategies - Bartosz L. Sikorski; Adriana Laudencka (Journal of Ophthalmology)
Purpose. To compare the results obtained with two threshold strategies of visual field assessment: Humphrey SITA Fast (SFA) (Carl Zeiss Meditec) and PTS 2000 Advanced Threshold (ADV) (Optopol Technology) in healthy subjects and patients with glaucoma. Methods. The study sample comprised of 53 healthy volunteers and 69 patients with glaucoma. One eye of each patient was examined with the SFA and ADV strategies. The quantitative comparisons of test duration and global indices were made using correlation coefficients. The sensitivity and specificity of the algorithms were evaluated based on the GHT results and the adjusted Anderson–Patella (A&P) criteria. Results. The ADV test duration was shorter both in healthy subjects (by 5%) and patients with glaucoma (by 18%). The mean differences in MS values between the SFA and the ADV strategies were 1.06 ± 1.13 dB (MSSFA-MSADV) in healthy subjects and 1.00 ± 1.92 dB (MSSFA-MSADV) in patients with glaucoma. The MD index of ADV tests was lower than the SFA in the healthy (−0.74 ± 1.09 dB) (MSSFA-MSADV) and glaucoma group (−0.85 ± 2.19 dB) (MSSFA-MSADV). The mean differences in PSD values determined using both methods were −0.86 ± 0.67 dB (PSDSFA-PSDADV) and −0.53 ± 1.48 dB (PSDSFA-PSDADV) in healthy subjects and patients with glaucoma, respectively. Analysis of receiver operating characteristic curves built from MD and PSD indices show bigger area under curve in SFA than in ADV (0.983 vs.0.968 and 0.986 vs. 0.938, respectively). The GHT-based sensitivity and specificity for the ADV strategy were 92.75% and 77.36%, respectively, as compared to 92.75% and 90.57%, respectively, for the SFA strategy. Conclusions. Both SFA and ADV enable effective identification of glaucomatous defects within 5 minutes. The ADV strategy, however, is significantly faster. The correlation between the global indices of SFA and ADV is very high. Both strategies offer very high sensitivity when using both GHT and A&P criteria.